(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The organization of emergency medical care is a key aspect of ensuring public health in emergency situations. An effective ambulance system can reduce mortality and disability from acute diseases, injuries, accidents, and disasters. One of the areas of healthcare development today is the improvement of the ambulance system. The problems of organizing and improving emergency medical care do not lose their relevance in the modern world and require further study. The need to optimize emergency care in family medicine centers has been identified in order to relieve the burden on the emergency medical care service.